1986
DOI: 10.1177/00220345860650050701
|View full text |Cite
|
Sign up to set email alerts
|

Correlated Observations and Analysis of Maturation-ameloblast Morphology and Enamel Mineralization

Abstract: A combined HCl-collagenase digestion technique and scanning electron microscopy were used to isolate the enamel organ and to confirm the presence of maturation ameloblasts of both ruffle-ended (RA) and smooth-ended (SA) types on maturing enamel in kitten permanent tooth germs. EDTA perfusion of animals fixed with aldehyde produced two or three belt-like shallow grooves (from 30 to 100 micron wide) running horizontally through the maturing enamel surface, coinciding closely with the SA distribution pattern. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
2
0

Year Published

1987
1987
1994
1994

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 14 publications
2
2
0
Order By: Relevance
“…Furthermore, there were no prominent differences in the mineral content of the matrices overlaid by ruffle-ended and smooth-ended maturation amcloblasts. A similar finding was recently reported for cat teeth (Debari et al, 1986). Electron-probe microanalysis of developing rat incisor enamel (Glick, 1979) also indicated a regular and progressive mineralization pattern in the enamel formation.…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, there were no prominent differences in the mineral content of the matrices overlaid by ruffle-ended and smooth-ended maturation amcloblasts. A similar finding was recently reported for cat teeth (Debari et al, 1986). Electron-probe microanalysis of developing rat incisor enamel (Glick, 1979) also indicated a regular and progressive mineralization pattern in the enamel formation.…”
Section: Discussionsupporting
confidence: 87%
“…Nevertheless, these surface analysis volumes represent enamel capable (or incapable, as the case may be) of being stained with GBHA and other dyes (McKee and Warshawsky, 1989), and consequently might have shown differences. The XRD, IR, XPS, and WDS analyses of both enamel strips gave spectra, electron binding energies, and Ca/P molar and intensity ratios consistent with those previously published for enamel (Landis and Navarro, 1983;Landis et al, 1982Landis et al, , 1988Debari et al, 1986;Sasaki et al, 1987). XRD indicated that the enamel examined was hydroxyapatite, and the other three techniques, while not definitive, supported this conclusion.…”
supporting
confidence: 85%
“…The data thereby derived from transversely-cut samples provide important but limited information on sequential organic and inorganic changes in enamel. In an effort to perform analyses while retaining ameloblast-enamel relations, Debari et al (1986) and Sasaki et al (1987) used scanning electron microscopy with electron probe x-ray micro-analysis on intact incisors to examine possible differences in enamel related to the two cell types. In addition, Bawden et al (1988) examined total Ca, Pi, F. and proline content relative to RA and SA.…”
mentioning
confidence: 99%
“…His findings are consistent with those reported in this study. Debari et al (1986) used physical assay methods in an effort to identify cell-typerelated changes in the mineral composition of the surface layer of forming kitten enamel. No clear relationship was established.…”
Section: Resultsmentioning
confidence: 99%